Investigating learners awareness on grammar in communication tasks learner interactions - Baharun H.; Zakaria A.R. (CRC Press/Balkema, 2024)
This paper reports on a study that investigates the use of communication tasks to elicit Language-Related Episodes (LREs) during learners oral interaction. Nine language learners in groups of three participated in the study. The participants completed two meaning-focused task types (i.e., jigsaw and decision-making) during which their learner interactions were recorded. Data were examined for instances of LRE. A qualitative analysis of the data revealed that the learners produced LREs during task completion for both tasks and paid considerable attention to grammar while engaged in meaning-focused communication tasks. This suggests that such tasks can be explored in promoting grammar awareness among learners as the grammar LREs produced during task completion may create opportunities for language development among the EFL learners. Results have practical implications for language teaching, research, and syllabus design. 2016 Taylor & Francis Group, London.